2002
DOI: 10.1074/jbc.m107942200
|View full text |Cite
|
Sign up to set email alerts
|

Human Class I Histone Deacetylase Complexes Show Enhanced Catalytic Activity in the Presence of ATP and Co-immunoprecipitate with the ATP-dependent Chaperone Protein Hsp70

Abstract: Antibodies to histone deacetylases (HDACs) have been used to immuno-isolate deacetylase complexes from HeLa cell extracts. Complexes shown to contain HDAC1, HDAC3, HDAC6, and HDAC1؉2 as their catalytic subunits have been used in an antibody-based assay that detects deacetylation of whole histones at defined lysines. The class II deacetylase HDAC6 was inactive in this assay, but the three class I enzymes deacetylated all histone lysines tested, although with varying efficiency. In comparison to HDAC1, HDAC3 pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 52 publications
1
84
0
Order By: Relevance
“…Although this approach does not provide pure enzymatic preparations, some differences in the preferred lysine residues of the individual complexes were observed. The in vitro results suggested that HDAC3 could completely deacetylate H2A, H4K5Ac and H4K12Ac, but only partially deacetylate H3, H2B, H4K8Ac and H4K16Ac (Johnson et al, 2002). Compared with HDAC1, HDAC3 deacetylated H4K8Ac, H4K16Ac and H2B at the same rate, but it deacetylated H4K5Ac, H4K12Ac and H2AK5Ac much more rapidly.…”
Section: Substrate Specificitymentioning
confidence: 93%
See 2 more Smart Citations
“…Although this approach does not provide pure enzymatic preparations, some differences in the preferred lysine residues of the individual complexes were observed. The in vitro results suggested that HDAC3 could completely deacetylate H2A, H4K5Ac and H4K12Ac, but only partially deacetylate H3, H2B, H4K8Ac and H4K16Ac (Johnson et al, 2002). Compared with HDAC1, HDAC3 deacetylated H4K8Ac, H4K16Ac and H2B at the same rate, but it deacetylated H4K5Ac, H4K12Ac and H2AK5Ac much more rapidly.…”
Section: Substrate Specificitymentioning
confidence: 93%
“…When targeted to preacetylated nucleosomal templates, Sin3/HDAC was found to deacetylate both H3 and H4, whereas the N-CoR/SMRT-HDAC3 complex displayed preferential activity toward H3 (Vermeulen et al, 2004). This result is somewhat surprising, considering the data discussed above (Johnson et al, 2002;Hartman et al, 2005). Future work is necessary to reconcile this difference.…”
Section: Substrate Specificitymentioning
confidence: 95%
See 1 more Smart Citation
“…A mouse monoclonal antibody raised against HDAC3, but recognising HDAC1, 2 and 3, was from BD Transduction Laboratories; we have confirmed the unusual specificity of this antibody by comparison with our own antisera specific for HDAC1, 2 or 3. 21 Bound antibody was detected either with peroxidaseconjugated anti-rabbit antibody and Enhanced ChemiLuminescence (ECL, Amersham-Pharmacia, UK) or with IRDye-800-conjugated, affinity-purified goat anti-rabbit secondary antibody followed by quantitation with an infra-red dye imaging system (LI-COR Biosciences Ltd, UK). The latter was used for all experiments with primary blast cells from patients.…”
Section: Sds Gels and Western Blottingmentioning
confidence: 99%
“…Hsp70 is an important cochaperone protein with Hsp90. It was reported that one of the class I HDACs is the deacetylase of Hsp70 and that romidepsin treatment can increase acetylation of Hsp70 (40). Of note, Hsp70 is required for the assembly of Hsp90-client protein complexes (41).…”
Section: Romidepsin Decreased the Binding Of Ahr To Hsp90 In The Respmentioning
confidence: 99%